Application of Sport Psychology in Team Management: Improving Athlete Performance and Wellbeing - Suyudi, Imam (Manunggal Halim Jaya, 2024)
This abstract explores the critical intersection of sport psychology and team management, emphasizing the importance of mental fortitude and psychological resilience in the pursuit of athletic excellence. Beyond physical prowess, this research underscores the role of psychological factors—motivation, confidence, focus, stress management, and mental health—in determining athletic outcomes. It advocates for a holistic approach to athlete development, integrating sport psychology into team management to optimize both performance and wellbeing. Through a comprehensive examination of empirically supported psychological strategies, including mindfulness, visualization, cognitive-behavioral interventions, and motivational interviewing, the study aims to offer practical, evidence-based recommendations for teams and coaches. This includes addressing individual and team performance enhancements, psychological assessments, goal setting, and mental imagery, as well as tackling psychological challenges like injuries, eating disorders, and career transitions. The research also delves into the dynamics between individual athletes and team objectives, the pivotal coach-athlete relationship, team cohesion, and the broader implications of mental training in athletic rehabilitation. By fostering an environment where athletes can excel and maintain their mental health, this theme ventures into redefining team management paradigms through the lens of sport science and psychology.